2018
DOI: 10.1111/cxo.12574
|View full text |Cite
|
Sign up to set email alerts
|

Autologous serum eye‐drops and enhanced epithelial healing time after photorefractive keratectomy

Abstract: Background: The aim of the study is to test whether use of autologous serum eye-drops can provide earlier epithelial healing following the application of photorefractive keratectomy. Method: Sixty patients (60 eyes) underwent photorefractive keratectomy for myopia. Thirty eyes received autologous serum drops (Study group) while 30 eyes received conventional artificial tears (Control group) after photorefractive keratectomy. An 8 mm epithelial opening was prepared with the application of 18 per cent alcohol for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
0
15
0
3
Order By: Relevance
“…The nerve growth factor induces an injured neuron’s function restoration that helps in corneal nerve regeneration [ 31 ]. However, in the results obtained by Akcam et al [ 17 ], the AS reduced pain score and reepithelialization time compared to an artificial tears group. In their study, surgery was alcohol-assisted PRK.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The nerve growth factor induces an injured neuron’s function restoration that helps in corneal nerve regeneration [ 31 ]. However, in the results obtained by Akcam et al [ 17 ], the AS reduced pain score and reepithelialization time compared to an artificial tears group. In their study, surgery was alcohol-assisted PRK.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, PRGF has been studied in the dry eye disease (DED) assessment and after laser-assisted in-situ keratomileusis (LASIK) [ 12 ], as an accelerator of the healing process in PRK [ 13 ] in mice [ 14 ] and as a regenerator of the corneal nerves after LASIK [ 15 ]. Other studies have analyzed autologous serum effect on re-epithelialization time in laser-assisted subepithelial keratectomy (LASEK) [ 16 ] and PRK [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another randomized, double-masked and controlled parallel-group study 15 evaluating tear film thickness after treatment with artificial tears in patients with moderate dry eye disease, showed that a single instillation of trehalose (30 mg/mL) and sodium hyaluronate (1.5 mg/mL) increased the thickness of the tear film in patients with dry eye disease. The data also indicate a longer corneal retention of eye drops in the eyes that received trehalose.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery process, as well as its main symptoms, are directly related to the epithelialization process, which takes place after 3-7 days on average; once the corneal epithelium has completely covered the surface of the cornea, symptoms and visual quality improve dramatically. Symptoms that occur in the corneal epithelialization phase after PRK include pain, foreign body sensation, photophobia, and blurred vision [15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Platelet-derived preparations and autologous/allogeneic serum eye-drops (ASE) are used therapeutically for restoring the disturbed micro-environment of the ocular surface. They are rich in growth factors, cytokines, vitamins and minerals which are required for normal corneal epithelial homeostasis and can stimulate proliferation, differentiation, and migration on the ocular surface [79]. Autologous serum eye-drops are similar to human tears regarding components such as EGF, TGF-β, fibronectin, vitamin A and other common cytokines [73][74][75].…”
Section: Hemoderivativesmentioning
confidence: 99%